Preoperative risk classification using neutrophil–lymphocyte ratio and hydronephrosis for upper tract urothelial carcinoma. (31st July 2018) - Kohada, Yuki; Hayashi, Tetsutaro; Goto, Keisuke; Kobatake, Kohei; Abdi, Hamidreza; Honda, Yukiko; Sentani, Kazuhiro; Inoue, Shogo; Teishima, Jun; Awai, Kazuo; Yasui, Wataru; Matsubara, Akio
Abstract : Our suggested classification using preoperative neutrophil–lymphocyte ratio and hydronephrosis is simple and practical predictor of prognosis in patients with upper tract urothelial carcinoma. Abstract: Background: To improve the prediction of outcomes in patients who will undergo radical nephroureterectomy (RNU) for upper tract urothelial carcinoma (UTUC), we examined the preoperative prognostic factors and established a risk classification model. Methods: A total of 148 patients who underwent RNU without history of neo-adjuvant chemotherapy between 1999 and 2016 in Hiroshima University Hospital were retrospectively reviewed. Associations between preoperative/clinicopathological factors and outcomes including cancer-specific survival (CSS) and recurrence-free survival (RFS) were assessed. We specifically looked at neutrophil–lymphocyte ratio (NLR) due to growing evidence on its predictive role in cancer prognosis prediction. Results: Preoperative elevated neutrophil–lymphocyte ratio (pre-op NLR, ≥3.0) and hydronephrosis (≥grade 2) were associated with advanced pathological stage; and were identified as independent predictive factors of shorter CSS and RFS in univariate and multivariate analysis. We classified the patients in three groups using preoperative factors and found that the 5-year CSS was 94.5, 75.9 and 44.7% and the 5-year RFS was 74.3, 57.6 and 28.7% in the low-risk group (neither pre-op NLR nor hydronephrosis), intermediate-risk group (either pre-op NLR or hydronephrosis) and high-risk group (pre-op NLR and hydronephrosis), respectively. High-risk group had significantly worse CSS ( P = 0.0172) and RFS ( P = 0.0014) than intermediate-risk group and low-risk group (CSS ( P < 0.0001) and RFS ( P < 0.0001)). Conclusions: Elevated pre-op NLR and hydronephrosis were identified as independent prognostic factors in patients with UTUC. These simple preoperative factors can stratify three prognostic groups and may help urologists in clinical decision-making before RNU.